Synthesis, investigation of biological effects and in silico studies of new benzimidazole derivatives as aromatase inhibitors - Sağlık, Begüm Nurpelin; Şen, Ahmet Mücahit; Evren, Asaf Evrim; Çevik, Ulviye Acar; Osmaniye, Derya; Kaya Çavuşoğlu, Betül; Levent, Serkan; Karaduman, Abdullah Burak; Özkay, Yusuf; Kaplancıklı, Zafer Asım (Zeitschrift für Naturforschung C. A journal of biosciences, 2020)
Inhibition of aromatase enzymes is very important in the prevention of estrogen-related diseases and the regulation of estrogen levels. Aromatase enzyme is involved in the final stage of the biosynthesis of estrogen, in the conversion of androgens to estrogen. The development of new compounds for the inhibition of aromatase enzymes is an important area for medicinal chemists in this respect. In the present study, new benzimidazole derivatives have been designed and synthesized which have reported anticancer activity in the literature. Their anticancer activity was evaluated against human A549 and MCF-7 cell lines by MTT assay. In the series, concerning MCF-7 cell line, the most potent compounds were the 4-benzylpiperidine derivatives , , and with IC values of 0.032 ± 0.001, 0.024 ± 0.001, and 0.035 ± 0.001 µM, respectively, compared to the reference drug cisplatin (IC = 0.021 ± 0.001 µM). Then, these compounds were subject to further aromatase enzyme inhibition assays to determine the possible binding modes and interactions underlying their activity. Thanks to molecular docking studies, the effectiveness of these compounds against aromatase enzyme could be simulated. Consequently, it has been found that these compounds can be settled very properly to the active site of the aromatase enzyme.